2022
DOI: 10.3390/genes13050730
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-Related Traits and Risk of Migraine—A Potential Mechanism and Treatment Consideration

Abstract: Migraine and glucose-related (glycaemic) traits (fasting glucose, fasting insulin, and type 2 diabetes) are common and complex comorbid disorders that cause major economic and social burdens on patients and their families. Studies on the relationship between migraine and glucose-related traits have yielded inconsistent results. The purpose of this review is to synthesise and discuss the information from the available literature on the relationship between fasting glucose, fasting insulin, and type 2 diabetes (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 242 publications
1
10
0
Order By: Relevance
“…Recent research has shown that DENND1A is associated with insulin resistance (IR) in women with polycystic ovarian syndrome, indicating that metabolic dysfunction may play a pathophysiologic role [ 67 ]. Interestingly, migraine is associated with an increased risk of metabolic dysregulation, including IR [ 11 , 68 ]. Therefore, they are plausible biologically candidate genes for migraine and T2D.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent research has shown that DENND1A is associated with insulin resistance (IR) in women with polycystic ovarian syndrome, indicating that metabolic dysfunction may play a pathophysiologic role [ 67 ]. Interestingly, migraine is associated with an increased risk of metabolic dysregulation, including IR [ 11 , 68 ]. Therefore, they are plausible biologically candidate genes for migraine and T2D.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that the association between migraine and headache with T2D differs by sex [ 10 ], and females are at increased risk for migraine [ 24 ]. In addition, migraine and headaches are more prevalent in females than males, and sex hormones, particularly oestrogen and progesterone fluctuations, are thought to play an important role [ 11 , 25 ]. Therefore, we conducted sex-specific analyses to determine if the genetic relationship between migraine and headache with T2D differs by sex.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…IGF1 plays a major part in the regulation of body composition and glucose metabolism [ 52 , 53 ]. On the other hand, insulin resistance and its comorbidities of obesity might have a biological association with migraine headache [ 54 , 55 ]. Therefore, low IGF1 levels in migraineurs might be a marker or a consequence of abnormal glucose metabolism and obesity.…”
Section: Discussionmentioning
confidence: 99%
“…A high prevalence of glycemic traits such as insulin resistance (IR), hyperinsulinemia, hypoglycaemia, hyperglycaemia, and type 2 diabetes (T2D) is associated with migraine and headache (Cavestro et al 2007 ; Fagherazzi et al 2019 ; Gross et al 2019 ; Rainero et al 2005 ; Sacco et al 2014 ; Zhang et al 2020 ), which, along with the increased risk of cardiovascular diseases (Daghals et al 2022 ; Guo et al 2020 ; Malik et al 2015 ), contributes significantly to shorter life expectancy. Previous epidemiologic studies investigating the relationship between fasting glucose (FG), fasting insulin (FI), and glucose tolerance with migraine risk have produced conflicting findings (Islam and Nyholt 2022 ; Shaw et al 1977 ; Siva et al 2018 ). In addition, several studies have investigated the increased comorbidity of migraine and glycemic traits, focusing on the dysregulation of glucose (Hufnagl and Peroutka 2002 ; Zhang et al 2020 ) or dysglycaemia in migraine patients as possible outcome of disturbed metabolism mainly due to impaired glucose-insulin metabolism (Gross et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%